POLLEN RECORD OF THE PERMIAN MARINE SEDIMENTS FROM WEST TIMOR - Eko Budi Lelono (Testing Center for Oil and Gas LEMIGAS, 2017)
This is the fi rst publication to present palynological study on the Permian marine sediments of West Timor. This is aimed to evaluate its palynomorph content. Similar studies have been performed on the Permian sediments which mostly focus on non-marine sediments. 15 surface samples were collected from Lilana river outcrop which comprises the alternation of calcareous shale and sandstone. This outcrop is assumed to represent some parts of Bisane Formation. Standard preparation methods were employed to extract palynomorphs including acid maceration and oxidation. This study applies quantitative method which requires counting of palynomorphs in each sample. This study provides low to moderate pollen recovery which mostly consists of striate and non-striate bisaccates as well as trilete monosaccates. The age restricted taxa appearing in the non-marine sediments also present in the studied samples to mark Permian age such as Protohaploxypinus samoilovichi, Lunatisporites pellucidus, Falcisporites australis, Plicatipollenites malabarensis and Cannanoropollis janakii. On the other hand, common occurrence of marine dinofl agellates of Dapsilidium langii and Veryhachim reductum combined with abundant macrofossil of chrinoids confi rm a shallow marine paleoenvironment. Common green algae of Tasmanites sp. is a firmed evidence for the appearance of potential source rock of hydrocarbon within the Permian shallow marine sediments of West Timor.